Adhesive Behavior of Propolis on Different Substrates - Saccardi, Leonie; Schiebl, Jonas; Weber, Katharina; Schwarz, Oliver; Gorb, Stanislav; Kovalev, Alexander (Frontiers in Mechanical Engineering, 2021)
Propolis is a sticky substance used by bees to seal their hive and protect the colony against pathogens. Its main components are plant resins, beeswax, essential oils, pollen and other organic substances. The chemical and medicinal properties of propolis have been extensively studied, but little is known about its physical and especially adhesive properties. To gain a better understanding of propolis and its potential for adhesive applications, we performed several experiments, including adhesion tests with propolis in different conditions and on various substrates, differential scanning calorimetry analysis and compression tests. Propolis shows clear viscoelastic behaviour and temperature-dependent mechanical properties. Our results demonstrate that propolis adheres well to a wide range of substrates from glass to PTFE and stronger adhesion at higher temperatures and longer contact times. In wet conditions underwater, quite a substantial adhesion was also measured. The data are interpreted from biomechanical point of view and significance of obtained results for the bee biology is discussed.